ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN YANG TERCANTUM DALAM INDEKS LQ45 - Haidar Abdullah; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2015)
This study aimed to examine the effect of profitability ratio on stock price of companies listed in LQ45 index in Indonesia Stock Exchange (BEI). Profitability ratios here in include Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Eearning Per Share (EPS). This study was conducted to assess the financial performance of the company to generate earnings from an investment.This study uses secondary data. The population in this study is the companies included in the LQ45 index from 2010-2013 amounting to 78. The total sample is 16 companies belonging to and representing several sectors including the financial sector companies, automotive, property, plantation, infrastructure, mining, industrial cement, as well as the consumer goods industry are consistently incorporated in the four observation period 2010-2013 in LQ45 index that has been determined through purposive sampling method. Method of hypothesis testing using Classical Assumption Test, Regression, t test, F test, and the coefficient of determination by alpha (α) of 5%.Regression analysis showed that in partial Net Profit Margin (NPM), Return on Assets (ROA) and Return On Equity (ROE) significantly influence the stock price while the variable Eearning Per Share (EPS) has no significant effect on stock price. Simultaneously all variables Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Eearning Per Share (EPS) have a significant effect on stock price. The value of coefficient of determination (R2) of 0.899, which means that the independent variable Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Eearning Per Share (EPS) is able to explain the variation of the dependent variable stock price by 89,9%, while the remaining 10.1 % is explained by other variables outside of the variables used in the study.